La agroecología en el bachillerato técnico agropecuario del cantón Colta-provincia del Chimborazo. - Orozco González, Juan Manuel (2015)
In this research we analyzed the situation of the Agroecology Agricultural Technical high schools from Canton Colta, Chimborazo Province, which today are called Intercultural Bilingual Education Units, those were: Intercultural Bilingual Education Unit Duchicela Shyri XII, from Community Llinllín at Columbe Parish; Intercultural Bilingual Education Unit Jacobo Yepez, from Community Guacona small at the Sicalpa Parish and Intercultural Bilingual Education Unit General Rumiñahui, Community Lily al Sicalpa Parish. The methodology used in the study was based on gathering information from schools, by collecting statistical data and analysis of documents concerning institutional history, student records, records of teachers, curricula, teaching schedules. The results were analyzed and proceeded to conduct a preliminary proposal Agroecology curricular subject for agricultural technical schools in the canton Colta. In the final phase of the research findings and recommendations were established.